CIRI SINTAKSIS BAHASA BUGIS DI KALANGAN PERANTAU BUGIS DI JAYAPURA, PAPUA - Sukardi Gau (Balai Bahasa Provinsi Papua, 2019)
Syntax study of Buginese have done by some researcher. But linguistics research that focused to Buginese abroad poeple never do. So, this research explained to linguistics characters of Buginese poeple in Papua, especially about its syntax characters. Data was collected by observation and interview process. The conclude of this research was found three of sentence forms, that are content sentence, passive voice, negative sentence, imperarive, introgative, and compound sentence. Its examples was taken from the field research.